Valproic Acid-Induced Hyperammonemic Encephalopathy in a Patient with Bipolar Disorder: A Case Report - Meng-Yu Wu; Fang-Yu Chang; Jian-Yu Ke; Chien-Sheng Chen; Po-Chen Lin; Tzong-Shi Wang (Brain Sciences, 2020)
Valproic acid (VPA) is widely used to control various seizure disorders and psychiatric disorders. Valproic acid-induced hyperammonemic encephalopathy (VHE) is a rare but dangerous complication of VPA-induced toxicity. For this case report, several risk factors were identified, including young age, polytherapy regimens, VPA overdose, poor liver function, and carnitine deficiency. The detailed mechanisms of VHE remained unclear. Hyperammonemia may be caused by hypocarnitinemia, leading to imbalanced VPA metabolism. VHE may initially cause gastrointestinal symptoms, followed by a decreased level of consciousness and seizure. Early diagnosis of VHE is important for physicians for the timely reversal of VHE by discontinuing administration of VPA and administering lactulose or levocarnitine. Here, we describe a patient with a bipolar disorder who presented with VHE after receiving a strict vegetarian diet in our hospital. We recommend that VHE be included in the differential diagnosis of patients with high serum VPA levels and strictly vegetarian diets, especially those presenting with acute gastrointestinal symptoms.